The Students Facilitator and Explaining Learning Model to Improve Student Learning Achievement in Islamic Education Learning at SMP Negeri 2 Ulim - Zafira, Miska; Sriyani, Linda (Jurnal Cendekia Islam Indonesia, 2025)
This classroom action research aimed to improve students’ learning achievement on the topic Courtesy, Politeness, and Sense of Shame through the application of the Students Facilitator and Explaining (SFAE) learning model in Grade VIII/B of SMP Negeri 2 Ulim, Pidie Jaya Regency. The research subjects consisted of 25 students, and the study was conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. Data were collected through learning achievement tests, classroom observations, documentation, and interviews, and analyzed using both qualitative descriptive and quantitative approaches. The results showed a significant improvement in students’ learning outcomes and activeness after the implementation of the SFAE model. During the pre-cycle, only 7 students (28.00%) achieved the minimum mastery criterion (70). After the first cycle, the number increased to 17 students (68.00%), and in the second cycle, it reached 22 students (88.00%). The class average also rose from 60.0 in the pre-cycle to 69.6 in Cycle I and 80.6 in Cycle II. Furthermore, students demonstrated higher motivation, participation, and confidence in explaining lesson content. Thus, the SFAE model effectively created an interactive and engaging classroom atmosphere, significantly enhancing students’ achievement in Islamic Education and Character Building.